2018
DOI: 10.1051/itmconf/20181804007
|View full text |Cite
|
Sign up to set email alerts
|

Children's perception of parental attitudes: Russia-Kyrgyzstan cross-cultural study

Abstract: The article presents the results of a cross-cultural analysis of the perception of parental attitude by children and adolescents. We focused on the indicators of maternal and paternal attitude such as Acceptance, Positive Involvement, Rejection and Hostile Detachment. The Russian sample includes 501 primary school students aged 6.8 to 11.7 years (49.9% boys) and 438 adolescents aged 10.8 to 16.8 years (47.1% boys). The Kyrgyz sample includes 510 primary school students aged from 6.6 to 11.8 years (48.5% boys) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to previous studies, mothers and fathers organize the relationships with their child, participate in children's activities and demonstrate their attitude in different ways (Tikhomirova & Malykh, 2018). Previous studies demonstrated that the differences are related to the level of involvement in child's activities, satisfaction of child's needs and desires, and support of the information flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, mothers and fathers organize the relationships with their child, participate in children's activities and demonstrate their attitude in different ways (Tikhomirova & Malykh, 2018). Previous studies demonstrated that the differences are related to the level of involvement in child's activities, satisfaction of child's needs and desires, and support of the information flow.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the perception of attitudes, differences were revealed between maternal and paternal attitude both for Acceptance and Positive Involvement. In particular, primary school children assessed maternal attitude as more emotionally accepting than paternal attitude (Tikhomirova & Malykh, 2018).…”
Section: Introductionmentioning
confidence: 99%